Methodical issues of the ethnopolitical and ethnosocial processes’ empirical researches in the regions of the Russian Arctic - Anton M. Maksimov; Ilya F. Vereschagin; Maksim Yu. Zadorin (Arctic and North, 2018)
The article considers the methodic aspects of empirical ethnopolitical and ethno-social research in the regions of the modern Russia. It is demonstrated that the tools for quantitative sociological research of interethnic and interdenominational relations should be adapted for large-scale cultural-historical groups of the regions. E.g., in the case of the Russian Arctic, the indigenous small-numbered peoples are an important subject of the ethnic policy, which requires the use of additional indicators that represent their cultural development and participation in ethnopolitical relations. The toolkit of empirical cross-regional studies usually includes the measurement of individual variables. The article proposes a more complex and systematic methodology based on the idea of constructing integral indices, aggregating the values of a set of related indicators. To analyze the dynamics of the ethnic components of the region's social system, a set of categories is proposed, through which it is possible to describe the configuration of the main ethnic actors and the state of political and cultural institutions. The categories were operationalized for the political, societal and socio-cultural subsystems of the region, resulting in a system of indicators for monitoring ethnopolitical and ethno-social processes. The article shows an example of the procedure for constructing an integral index of the ethnic policy' quality (nationalities policy index) based on indicators proposed by the authors for measuring ethnopolitical processes in the region. In the end of the paper, the major issues for the measuring the data unification got with the use of different methods from qualitatively different sources is set.